1999
DOI: 10.1007/s002130051065
|View full text |Cite
|
Sign up to set email alerts
|

Discriminative stimulus effects of ethyl-β-carboline-3-carboxylate at two training doses in rats

Abstract: These results indicated that the stimulus effects of the high dose of beta-CCE appeared consistent with mediation by the drug's partial inverse agonist effects at BZ receptors. The discriminative stimulus effects of beta-CCE at the lower training dose, however, appeared to be relatively non-specific.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
2
4
0
Order By: Relevance
“…Similar pA 2 values for flumazenil in rats discriminating pregnanolone or midazolam indicated that effects of midazolam and flunitrazepam are mediated by the same population of receptors in the two groups. The pA 2 values for flumazenil obtained in the current study are similar to those reported for flumazenil in another study in which it antagonized the discriminative stimulus effects of β-CCE, a negative GABA A modulator acting at benzodiazepine sites (Rowlett et al 1999). Although the discriminative stimulus effects of β-CCE are very different from those of benzodiazepines (current study; Rowlett et al 1999; Lelas et al 2000), similar pA 2 values for flumazenil indicate that the same population of receptors mediates their effects.…”
Section: Discussionsupporting
confidence: 89%
“…Similar pA 2 values for flumazenil in rats discriminating pregnanolone or midazolam indicated that effects of midazolam and flunitrazepam are mediated by the same population of receptors in the two groups. The pA 2 values for flumazenil obtained in the current study are similar to those reported for flumazenil in another study in which it antagonized the discriminative stimulus effects of β-CCE, a negative GABA A modulator acting at benzodiazepine sites (Rowlett et al 1999). Although the discriminative stimulus effects of β-CCE are very different from those of benzodiazepines (current study; Rowlett et al 1999; Lelas et al 2000), similar pA 2 values for flumazenil indicate that the same population of receptors mediates their effects.…”
Section: Discussionsupporting
confidence: 89%
“…DMCM did not antagonize pregnanolone at the same doses that antagonized midazolam, and doses of DMCM larger than 3.2 mg/kg were not tested in combination with pregnanolone because seizures occurred with these doses in diazepam-treated monkeys. That β-CCE, and not DMCM, antagonized pregnanolone is consistent with a previous study demonstrating that β-CCE and DMCM did not share discriminative stimulus effects (Rowlett et al 1999). The antagonism of pregnanolone by negative modulators (β-CCE and β-CCM) could involve two different sites that are allosterically linked to the same Cl − ionophore.…”
Section: Discussionsupporting
confidence: 81%
“…Two stand-alone investigations provide preliminary insights into the role of training dose for the α 1 -subunit selective agonist alpidem (Sanger and Zivkovic, 1994) and the partial inverse agonist β-CCE (Rowlett et al, 1999). Numerous studies demonstrated that benzodiazepine training dose magnitude was inversely proportional to the number of sessions to discrimination criteria in rats (Bruner and Anderson, 2009; De Vry and Slangen, 1986b; Shannon and Herling, 1983; Tang and Franklin, 1991; Sanger and Zivkovic, 1994; Rowlett et al, 1999) and gerbils (Järbe and Swedberg, 1998).…”
Section: Gaba-mimeticsmentioning
confidence: 99%
“…Two stand-alone investigations provide preliminary insights into the role of training dose for the α 1 -subunit selective agonist alpidem (Sanger and Zivkovic, 1994) and the partial inverse agonist β-CCE (Rowlett et al, 1999). Numerous studies demonstrated that benzodiazepine training dose magnitude was inversely proportional to the number of sessions to discrimination criteria in rats (Bruner and Anderson, 2009; De Vry and Slangen, 1986b; Shannon and Herling, 1983; Tang and Franklin, 1991; Sanger and Zivkovic, 1994; Rowlett et al, 1999) and gerbils (Järbe and Swedberg, 1998). It is similarly well documented that lower benzodiazepine training doses are associated with a leftward shift in the dose-response curve (i.e., lower ED 50 ) when compared to higher doses of the same training drug in rats (Ator and Griffiths, 1989; De Vry and Slangen, 1986b, 1986b; Bruner and Anderson, 2009; Sannerud and Ator, 1995a, 1995b; Shannon and Herling, 1983; Tang and Franklin, 1991; Sanger and Zivkovic, 1994; Rowlett et al, 1999) and humans (Rush et al, 1995).…”
Section: Gaba-mimeticsmentioning
confidence: 99%